PENGARUH GUGATAN GANTI RUGI TERHADAP KEBIJAKAN PENENTUAN LABA DALAM LAPORAN KEUANGAN : PENGUJIAN LITIGATION HYPOTHESIS PERUSAHAAN INDONESIA - Putra, Wahyu Manuhara (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
The purpose of this study was to examine the effect of the event or events (insident) litigation against the policy determination of the profits. The sample was perushaaan listed on the Jakarta Stock Exchange (JSX) from 1993-2006. The results of this study found no effect of compensation in respect of the determination of the profit for the company policy in a period of dispute relative to the period not as a defendant.